Socio-Demographic and Clinical Profile of People Living with HIV/AIDS. - Khan, MA; Sharma, Shashi (Asian Journal of Medical Sciences, 2013)
Although India is in the grip of HIV/AIDS epidemic, not much information is available on socio-demographic and clinical aspects of people living with HIV/AIDS (PLWHA). The present study has been designed with the following objective. Objectives: To assess the socio-demographic and clinical profile of people living with HIV/AIDS (PLWHAs) in India. Material and methods: The study was carried among 251 HIV/AIDS positive persons attending the out-patients department at the antiretroviral treatment (ART) clinic of the HIV testing centers at three major govt. hospital of Delhi, India. All the patients, male and female in the age range of 20-65 years and willing to participate were included in this study during the period 2007-2009. Written as well as informed consent was obtained for each patient at the time of recruitment. The HIV status was analyzed by ELISA with further confirmation by western blot; CD4/CD8 counts were measured by a flow-cytometer. Statistical analysis was carried out using chi-square test in order to see the association between age groups for various psychological measures and for treatment responses of the participants receiving ART. Results: Majority of the patients (77.7%) were found to be young (<40 years) and married (86.9 %). As high as 61.8% came from low socio-economic class and more than 93.6% acquired HIV transmission through heterosexual routes. A large proportion of these patients reported an extremely high level of anxiety, moderate level of stress and a borderline level of clinical depression. While some of the patients (28.3%) were well-adjusted with the ART, the rest of the patients reported difference in making adjustment with the treatment schedules. Conclusion: The study suggests that counselling and supportive therapy could play a pivotal role in controlling anxiety, stress, depression and rehabilitating people with HIV/AIDS. Thus, proper preventive intervention among general population and establishment of proper laboratory support is recommended. DOI: http://dx.doi.org/10.3126/ajms.v3i2.5039 Asian Journal of Medical Sciences 3(2012) 1-10